PENERAPAN MODEL PEMBELAJARAN INKUIRI MELALUI PENDEKATAN EKOLITERASI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI PENCEMARAN LINGKUNGAN - Baiq Salsabila Tulmaqwan; Ramdhani Sucilestari; Muhammad Anwar Sani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low critical thinking skills of fifth-grade students at MI Nurul Islam Ganti, especially on environmental pollution material. The problem was caused by the use of conventional teaching methods, particularly the lecture method, which made students passive during the learning process. This study aimed to improve students’ critical thinking skills through the implementation of the inquiry learning model with an ecoliteracy approach. The research employed Classroom Action Research (CAR) conducted in two cycles. The subjects of the study were 20 fifth-grade students of MI Nurul Islam Ganti. Data were collected through observations of teacher activities, observations of student activities, and essay tests measuring students’ critical thinking skills. The results showed that the implementation of the inquiry learning model through the ecoliteracy approach effectively improved students’ critical thinking skills on environmental pollution material. In the first cycle, 7 students were categorized as highly critical, 6 students as critical, and 7 students as moderately critical. In the second cycle, 19 students achieved the highly critical category and 1 student was categorized as moderately critical. Teacher activity increased from 85.29% in the first cycle to 94.11% in the second cycle, while student activity increased from 62.5% to 70.5%. These findings indicate that the inquiry learning model with an ecoliteracy approach is effective in improving students’ critical thinking skills.